Relação entre umidade, oleosidade e temperatura e população de fungos patogênicos em diferentes áreas anatômicas de cães com e sem dermatopatias - Pereira, Tânia Mara Mariano (2020)
Malassezia pachydermatis and dermatophyte fungi are fungal microorganisms associated with dermatopathies in dogs, but which can also be present in the canine integument as saprophytic microorganisms. The factors that modulate the migration of these agents, from the condition of saprophyte to pathogen, are little known. The present study evaluated the influence of moisture, oiliness and skin temperature of dogs on the population of yeasts of the genus Malassezia and dermatophytes, in 58 dogs with and 69 without skin diseases, regardless of age, race and sex. Moisture and oiliness were measured by bioimpedance instrumenr in four anatomical areas: frontal area of the head (AFC), left and right axillae (AAD e AAE) and lumbosacral area (ALS). At these same points, the temperature of the skin surface was assessed by infrared thermometer and skin samples were collected with sterile carpet strips and subjected to quantitative culture for Malassezia and dermatophytes, with values expressed in CFU / strip. The interrelation between the data was assessed by principal component analysis (PCA). In the ADE, temperature, humidity and oiliness were higher than the others. ACPs revealed that moisture and oilness interact independently of the population of fungal pathogens, in AFC and ADE. In ALS, dermatophytes appear to interact with skin oilness. Dogs with skin disorders have a wider range of results and interactions in the ADE and ALS than dogs without skin diseases. It is concluded that different anatomical areas may present homeostatic factors that regulate the population of fungal pathogens.